A biochar-based three-dimensional porous electrode material, a method for preparing an electrode, and an application of the electrode
By using biochar-based three-dimensional porous electrode materials in an anaerobic digestion system, combined with bioelectrochemical technology, the problem of accumulation of intermediate metabolites under high organic loads is solved, and the methane yield and system stability are significantly improved.
Patent Information
- Application Number
- CN202310793495.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-06-30
AI Technical Summary
The existing anaerobic digestion technology can easily lead to the accumulation of intermediate metabolites under high organic load conditions, leading to inhibition of microbial activity, and thus affecting the operating efficiency and stability of the system.
Biochar-based three-dimensional porous electrode materials are used to combine anaerobic digestion technology with bioelectrochemistry to treat sewage through electrolysis and reduce the risk of accumulation of intermediate metabolites.
It significantly improves the metabolic activity of methanogenic microorganisms, increases the methane yield, reduces the acidification of the reaction solution, and improves the stability and efficiency of the anaerobic digestion system.
Smart Images

Figure CN117923642B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a biochar-based three-dimensional porous electrode material, an electrode preparation method and electrode applications, and belongs to the technical field of organic waste treatment. Background Art
[0002] Anaerobic digestion technology is an environmentally friendly organic waste treatment technology that can achieve the "three-transformation" treatment of organic waste and obtain clean energy biogas at the same time. Methane production is the last stage of anaerobic digestion and is the most sensitive stage to the imbalance of the reaction process in engineering applications. This is due to the low abundance and functional redundancy of methanogens in the system, which makes the methanogenesis process easily inhibited. In a specific application environment, it is often difficult to achieve the combined anaerobic digestion of the target substrate and its adapted raw materials. In the anaerobic digestion system, acid-prone and nitrogen-rich raw materials have a nutritional imbalance with fermentation microorganisms, which causes the accumulation of intermediate metabolites and the inhibition of microbial life activities. This is the main reason for the low operating efficiency, poor stability, low gas production and poor energy quality of the anaerobic digestion system. At present, a variety of solutions have been proposed for this problem, but due to the technical and economic limitations of each approach, it is difficult to effectively solve the above problems fundamentally. Summary of the invention
[0003] To address the deficiencies in the prior art, the present invention provides a biochar-based three-dimensional porous electrode material, an electrode preparation method, and the application of the electrode in high organic load anaerobic digestion. By combining anaerobic digestion technology with bioelectrochemistry, the risk of accumulation of intermediate metabolites (organic acids, ammonia nitrogen) in anaerobic reactors under high organic load impact is minimized.
[0004] The technical solution adopted by the present invention is:
[0005] A method for preparing a biochar-based three-dimensional porous electrode material, the preparation method being as follows:
[0006] The straw biomass powder is immersed in NH3·H2O solution for pretreatment, the pretreated straw powder is subjected to anaerobic pyrolysis to obtain straw native biochar, and the straw native biochar is then sequentially immersed in alkali solution, activated at high temperature, cleaned with acid solution, and washed with water to obtain the electrode material.
[0007] Preferably, in the pretreatment, the concentration of NH3·H2O solution is 10-20%, and the soaking time is ≥24 hours; the soaking ratio of straw biomass powder to NH3·H2O solution is 25 g: (300-600) mL;
[0008] In the alkali solution impregnation, the alkali solution is a NaOH solution with a concentration of 5-10%, and the impregnation time is ≥24 hours; the impregnation ratio of straw biomass powder to alkali solution is 10 g: (35-60) mL;
[0009] In the acid cleaning, the acid is a HCl solution with a concentration of 10-25%, and the acid cleaning time is 5-20 minutes; the cleaning ratio of straw biomass powder to acid is 10 g: (85-120) mL.
[0010] Preferably, the anaerobic pyrolysis conditions are: in a nitrogen atmosphere, the heating rate is 1-5 °C·min -1 , pyrolysis temperature 300~700℃, pyrolysis time 2 h;
[0011] The high temperature activation conditions are: heating rate 3-8℃·min -1 , activation temperature 850-1000℃, activation time 0.5-2h.
[0012] Preferably, the electrode material has a particle size of 100-200 μm, a particle hardness of ≥85%, and an apparent density of 0.5-2.0 g / cm 3 , specific surface area 500-700 m 2 ·g -1 .
[0013] A method for preparing a biochar-based three-dimensional porous electrode comprises the following steps:
[0014] S1: The electrode material prepared by the above method is mixed with carboxymethyl chitosan and a solvent, and then dispersed evenly, and heated and stirred until viscous, to obtain a cross-linked layer 1 of a biochar-based porous three-dimensional electrode; wherein the addition ratio of the electrode material to carboxymethyl chitosan and the solvent is (3-8) g: 1 g: (12-20) ml;
[0015] S2: The electrode material prepared by the above method is mixed with acrylic resin emulsion and solvent, dispersed evenly, and heated and stirred until viscous to obtain the second cross-linked layer of the biochar-based porous three-dimensional electrode; wherein the addition ratio of the electrode material to the acrylic resin emulsion and solvent is (2-5) g:2 g:(14-20) ml;
[0016] S3: Rolling the cross-linked layer 1 and the cross-linked layer 2 of the biochar-based porous three-dimensional electrode onto the upper and lower surfaces of the metal mesh respectively, and drying them to obtain the biochar-based porous three-dimensional electrode.
[0017] Preferably, in step S1, the preparation method of the carboxymethyl chitosan is as follows: chitosan is swelled with isopropanol for 0.5-1.5h and then alkalized, and then an isopropanol solution containing sodium chloroacetate is added, and the reaction is carried out at 45-67°C for 4-6h; the pH of the system is adjusted to neutral and then allowed to stand; after removing the supernatant, the solution is filtered by suction, and the residue is dissolved with water and then filtered to remove impurities, rotary evaporated, and ethanol is added to the filtrate under stirring until a large amount of flocs are precipitated, allowed to stand and then centrifuged for washing, and dried at 50-70°C to obtain carboxymethyl chitosan;
[0018] The addition ratio of chitosan, isopropanol and isopropanol solution containing sodium chloroacetate is: 1 g: (8-15) ml: (7-12) ml; and in the isopropanol solution containing sodium chloroacetate, the ratio of sodium chloroacetate to isopropanol solution is (3-6) g: 10 ml.
[0019] Preferably, the specific method of the alkalization treatment is: dropwise adding 110-140 ml of 10 mol / L NaOH solution into the system, and stirring at room temperature for 1.5-3 h.
[0020] Preferably, in steps S1 and S2, the heating temperature is 110-125° C.; in step S3, the drying condition is: drying at 40-60° C. for 18-30 hours.
[0021] Preferably, in step S3, the pore size of the metal mesh is in the range of 0.5-1.5 mm.
[0022] The biochar-based three-dimensional porous electrode prepared by the above method is used in high organic load anaerobic digestion, and the sewage is treated by electrolysis, and the biochar-based three-dimensional porous electrode is used as the cathode.
[0023] The beneficial effects of the present invention are:
[0024] 1. Biochar-based electrode materials are widely available and have low preparation costs. In terms of the selection of raw materials for electrode materials, materials such as graphene and carbon nanotubes are expensive and cannot be mass-produced. Straw biomass, as a common agricultural waste, has a short growth cycle, low collection cost, and a wide and stable source, making it an excellent biomass raw material;
[0025] 2. Carboxymethyl chitosan and acrylic resin emulsion can produce self-crosslinking, which makes the obtained electrode more physically stable and will not cause the loss of electrode materials after long-term use;
[0026] 3. The biochar-based porous three-dimensional electrode of the present invention has a significant selective colonization effect on Methanosarcina and Methanobacterium according to tests, improving the metabolic activity of methanogenic microorganisms and increasing the methane yield by 95%;
[0027] 4. The use of the biochar-based porous three-dimensional electrode of the present invention and cheap electrical energy as excitation energy can quickly start the high-load impact anaerobic digestion methane production process and effectively prevent the startup failure caused by excessive acidification of the reaction solution due to high-load impact. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Flow chart for the preparation of biochar-based electrode materials;
[0029] Figure 2 is the SEM image corresponding to the biochar-based electrode material in Examples 1-3;
[0030] Figure 3 It is a map of the diversity of methanogenic microorganisms on biochar-based porous three-dimensional electrode biofilm. DETAILED DESCRIPTION
[0031] The present invention will be specifically described below in conjunction with the accompanying drawings and embodiments.
[0032] like Figure 1 As shown, the steps for preparing the biochar-based electrode material provided by the present invention are as follows:
[0033] Step 1: Collect seasonal biomass straw raw materials, crush and dry them with a high-speed crusher, sieve them with 80-100 mesh, and the particle size is less than 180 μm. According to the ratio of 10-20% NH3·H2O 500 mL and corn straw powder 25 g, soak the corn straw powder in NH3·H2O for 24-48 hours, and then place the pretreated corn straw powder mixture in an 80 ℃ drying oven to evaporate to dryness, so as to obtain biomass straw powder pretreated with ammonia water;
[0034] Step 2: Place the biomass straw powder pretreated with ammonia water in a vacuum tube furnace and blow in high-purity nitrogen at a flow rate of 0.7 L / min for 1 hour to ensure that the vacuum tube furnace is oxygen-free. Use a slow pyrolysis process with a heating rate of 3°C min -1 , keep the final temperature at 300-700℃ for 2 h, cool naturally, crush again, sieve through 80-100 mesh, and obtain the original biochar;
[0035] Step 3: Place the original biochar in a NaOH solution at a ratio of 10 g of original biochar to 50 mL of 5-10% NaOH solution for 24 hours, and then perform high-temperature activation again under a nitrogen atmosphere. The final temperature is 900 °C and the heating rate is 5 °C min -1 , maintain for 1h;
[0036] Step 4: 10 g of activated raw biochar was immersed in 100 mL of 10-25% HCl solution for acid washing for 5-20 min, then repeatedly washed with deionized water until neutral, filtered, and dried in a forced air drying oven at 120 °C for 24 hours to construct a biochar-based electrode material with a microporous and mesoporous interconnected structure. The electrode material had a particle size of <200 μm, a particle hardness (ball milling method) of ≥85%, and an apparent density of 1.0-2.0 g / cm 3 , specific surface area 500-700 m 2 ·g -1 , this electrode material is named PBC700.
[0037] The steps for preparing the biochar-based electrode provided by the present invention are as follows:
[0038] Step 5: 5 g of biochar-based electrode material, 1 g of carboxymethyl chitosan and 15 mL of water are ultrasonically dispersed for 30 min to form a uniform mixed system A, and the mixed system A is heated and stirred at 110-125°C until it becomes viscous to obtain a cross-linked layer 1 of the biochar-based porous three-dimensional electrode;
[0039] Step 6: 3 g of biochar-based electrode material, 2 g of acrylic resin emulsion and 15 mL of water are ultrasonically dispersed for 30 min to form a uniform mixed system B, and the mixed system B is heated and stirred at 110-125°C until it becomes viscous to obtain the cross-linked layer 2 of the biochar-based porous three-dimensional electrode;
[0040] Step 7: The cross-linked layer 1 and the cross-linked layer 2 of the biochar-based porous three-dimensional electrode are respectively rolled onto the upper and lower surfaces of a metal mesh with a pore size of 0.5-1.5 mm, with a total thickness of 0.5 mm, placed in a forced air drying oven at 65°C for 24 hours, and then calcined at 700°C for 1 hour. After annealing, the mixture is naturally cooled to 25°C to obtain a biochar-based porous three-dimensional electrode.
[0041] Experimental method: The biochar-based porous three-dimensional electrode was placed in a single-chamber anaerobic reactor as the cathode, and a common graphite plate electrode was used as the anode. 1000 mL of organic wastewater with an initial COD concentration of about 10,000 mg / L was injected. A regulated DC power supply was used, and the voltage was controlled at -1.0~0 V. The wastewater was electrolyzed for 24-72 hours. After the biofilm was formed, the power supply was disconnected. The diversity of methanogenic microorganisms on the electrode biofilm was observed. Figure 3 At a certain time interval, a proper amount of feed liquid is taken out from the reactor to test various indicators of the feed liquid. The feed liquid analysis method is carried out in accordance with GB11914-89, and the chemical oxygen demand COD value is determined by potassium dichromate method.
[0042] In the following examples and comparative examples, the preparation method of carboxymethyl chitosan is as follows: 10g chitosan is dissolved in 100ml isopropanol for 0.5-1.5h, 120ml of 10mol / L NaOH solution is added dropwise to the system, stirred at room temperature for 1.5-3h, and then 100ml of isopropanol solution containing 40g sodium chloroacetate is added, and the reaction is carried out at 45-67°C for 4-6h; the pH of the system is adjusted to neutral and then allowed to stand; after removing the supernatant, the solution is filtered by suction, and the residue is dissolved in water and then filtered to remove impurities, rotary evaporated, and ethanol is added to the filtrate under stirring until a large amount of flocs are precipitated, allowed to stand and then centrifuged for washing, and dried at 65°C to obtain carboxymethyl chitosan.
[0043] The present invention is described below with reference to some examples. Example 1
[0044] Step 1: collect corn stalks of the season, crush and dry them with a high-speed crusher, sieve them with 80 mesh, and the particle size is less than 180 μm. According to the ratio of 500 mL of 20% NH3·H2O and 25 g of corn stalk powder, immerse the corn stalk powder in NH3·H2O for 24 hours, and then place the pretreated corn stalk powder mixture in an 80 ℃ drying oven to evaporate to dryness, so as to obtain corn stalk powder pretreated with ammonia water;
[0045] Step 2: Place the corn straw powder pretreated with ammonia water in a vacuum tube furnace and blow in high-purity nitrogen at a flow rate of 0.7 L / min for 1 hour to ensure that the vacuum tube furnace is oxygen-free. Use a slow pyrolysis process with a heating rate of 3°C min -1 , the final temperature was maintained at 700℃ for 2 h, cooled naturally, crushed again, sieved through 80 mesh, and the original biochar was obtained;
[0046] Step 3: Place the original biochar in a NaOH solution at a ratio of 10 g of original biochar to 50 mL of 10% NaOH solution for 24 hours, and then perform high-temperature activation again under a nitrogen atmosphere. The final temperature is 900 °C and the heating rate is 5 °C min -1 , maintain for 1h;
[0047] Step 4: 10 g of activated raw biochar was immersed in 100 mL HCl solution with a concentration of 25% for acid washing for 5 min, then repeatedly washed with deionized water until neutral, filtered, and dried in a forced air drying oven at 120 °C for 24 h to construct a biochar-based electrode material with a microporous and mesoporous interconnected structure. The electrode material had a particle size of 175 μm, a particle hardness (ball milling method) ≥ 85%, and an apparent density of 2.0 g / cm 3 , specific surface area 520 m 2 ·g -1 The electron microscope scanning image of the electrode material's apparent characteristics is shown in Figure 2 In the middle a region, this electrode material is named PBC-1;
[0048] Step 5: 5 g of biochar-based electrode material, 1 g of carboxymethyl chitosan and 15 mL of water were ultrasonically dispersed for 30 min to form a uniform mixed system A, and the mixed system A was heated and stirred at 115°C until it became viscous to obtain a cross-linked layer 1 of the biochar-based porous three-dimensional electrode;
[0049] Step 6: 3 g of biochar-based electrode material, 2 g of acrylic resin emulsion and 15 mL of water were ultrasonically dispersed for 30 min to form a uniform mixed system B, and the mixed system B was heated and stirred at 115°C until it became viscous to obtain the cross-linked layer 2 of the biochar-based porous three-dimensional electrode;
[0050] Step 7: The cross-linked layer 1 and the cross-linked layer 2 of the biochar-based porous three-dimensional electrode are respectively rolled onto the upper and lower surfaces of a metal mesh with a pore size of 0.5-1.5 mm, with a total thickness of 0.5 mm, placed in a forced air drying oven at 65°C for 24 hours, and then naturally cooled to 25°C to obtain a biochar-based porous three-dimensional electrode. Example 2
[0051] Step 1: Collect wheat straw of the season, crush and dry it with a high-speed crusher, sieve it with 100 mesh, and the particle size is less than 150 μm. Soak the wheat straw powder in NH3·H2O for 48 hours according to the ratio of 10% NH3·H2O 500 mL and wheat straw powder 25 g. Then, place the pretreated wheat straw powder mixture in an 80 ℃ drying oven and evaporate it to dryness to obtain wheat straw powder pretreated with ammonia water.
[0052] Step 2: Place the wheat straw powder pretreated with ammonia water in a vacuum tube furnace and blow in high-purity nitrogen at a flow rate of 0.7 L / min for 1 hour to ensure that the vacuum tube furnace is oxygen-free. Use a slow pyrolysis process with a heating rate of 3 °C min -1 The final temperature was maintained at 500 °C for 2 h, cooled naturally, crushed again, and sieved through 100 mesh to obtain the original biochar;
[0053] Step 3: Place the original biochar in a NaOH solution at a ratio of 10 g of original biochar to 50 mL of 5% NaOH solution for 24 hours, and then perform high-temperature activation again under a nitrogen atmosphere. The final temperature is 900 °C and the heating rate is 5 °C min -1 , maintain for 1h;
[0054] Step 4: 10 g of activated raw biochar was immersed in 100 mL HCl solution with a concentration of 10% for 20 min, then washed repeatedly with deionized water until neutral, filtered, and dried in a forced air drying oven at 120 °C for 24 h to construct a biochar-based electrode material with a microporous and mesoporous interconnected structure. The electrode material had a particle size of 145 μm, a particle hardness (ball milling method) ≥ 85%, and an apparent density of 1.5 g / cm 3 , specific surface area 680 m 2 ·g -1 The electron microscope scanning image of the electrode material's apparent characteristics is shown in Figure 2 In the middle b area, this electrode material is named PBC-2;
[0055] Step 5: 5 g of biochar-based electrode material, 1 g of carboxymethyl chitosan and 15 mL of water were ultrasonically dispersed for 30 min to form a uniform mixed system A, and the mixed system A was heated and stirred at 115°C until it became viscous to obtain a cross-linked layer 1 of the biochar-based porous three-dimensional electrode;
[0056] Step 6: 3 g of biochar-based electrode material, 2 g of acrylic resin emulsion and 15 mL of water were ultrasonically dispersed for 30 min to form a uniform mixed system B, and the mixed system B was heated and stirred at 115°C until it became viscous to obtain the cross-linked layer 2 of the biochar-based porous three-dimensional electrode;
[0057] Step 7: The cross-linked layer 1 and the cross-linked layer 2 of the biochar-based porous three-dimensional electrode are respectively rolled onto the upper and lower surfaces of a metal mesh with a pore size of 0.5-1.5 mm, with a total thickness of 0.5 mm, placed in a forced air drying oven at 65°C for 24 hours, and then naturally cooled to 25°C to obtain a biochar-based porous three-dimensional electrode. Example 3
[0058] Step 1: Collect rice straw of the season, crush and dry it with a high-speed crusher, sieve it with 100 mesh, and the particle size is less than 150 μm. According to the ratio of 10% NH3·H2O 500 mL and rice straw powder 25 g, soak the rice straw powder in NH3·H2O for 48 hours, and then place the pretreated rice straw powder mixture in an 80 ℃ drying oven to evaporate to dryness to obtain rice straw powder pretreated with ammonia water;
[0059] Step 2: Place the rice straw powder pretreated with ammonia water in a vacuum tube furnace and blow in high-purity nitrogen at a flow rate of 0.7 L / min for 1 hour to ensure that the vacuum tube furnace is oxygen-free. Use a slow pyrolysis process with a heating rate of 3 °C min -1 The final temperature was maintained at 500 °C for 2 h, cooled naturally, crushed again, and sieved through 100 mesh to obtain the original biochar;
[0060] Step 3: Place the original biochar in a NaOH solution at a ratio of 10 g of original biochar to 50 mL of 5% NaOH solution for 24 hours, and then perform high-temperature activation again under a nitrogen atmosphere. The final temperature is 900 °C and the heating rate is 5 °C min -1 , maintain for 1h;
[0061] Step 4: 10 g of activated raw biochar was immersed in 100 mL HCl solution with a concentration of 10% for 20 min, then washed repeatedly with deionized water until neutral, filtered, and dried in a forced air drying oven at 120 °C for 24 h to construct a biochar-based electrode material with a microporous and mesoporous interconnected structure. The electrode material had a particle size of 120 μm, a particle hardness (ball milling method) ≥ 85%, and an apparent density of 1.2 g / cm 3 , specific surface area 590 m 2 ·g -1 The electron microscope scanning image of the electrode material's apparent characteristics is shown in Figure 2 In the middle c region, this electrode material is named PBC-3;
[0062] Step 5: 5 g of biochar-based electrode material, 1 g of carboxymethyl chitosan and 15 mL of water were ultrasonically dispersed for 30 min to form a uniform mixed system A, and the mixed system A was heated and stirred at 115°C until it became viscous to obtain a cross-linked layer 1 of the biochar-based porous three-dimensional electrode;
[0063] Step 6: 3 g of biochar-based electrode material, 2 g of acrylic resin emulsion and 15 mL of water were ultrasonically dispersed for 30 min to form a uniform mixed system B, and the mixed system B was heated and stirred at 115°C until it became viscous to obtain the cross-linked layer 2 of the biochar-based porous three-dimensional electrode;
[0064] Step 7: The cross-linked layer 1 and the cross-linked layer 2 of the biochar-based porous three-dimensional electrode are respectively rolled onto the upper and lower surfaces of a metal mesh with a pore size of 0.5-1.5 mm, with a total thickness of 0.5 mm, placed in a forced air drying oven at 65°C for 24 hours, and then naturally cooled to 25°C to obtain a biochar-based porous three-dimensional electrode.
[0065] The biochar-based porous three-dimensional electrode obtained in Example 1-3 was placed as a cathode in a single-chamber anaerobic reactor, and an ordinary graphite plate electrode was used as an anode. Simulated organic wastewater with an initial COD concentration of 9987 mg / L and a pH value of 7.0 was injected, wherein the inoculated sludge was taken from an anaerobic reactor operating normally in the laboratory, 30 g of glucose, 1 g of urea, 250 mg of NaCl, 100 mg of KCl, 4.5 g of NaH2PO4, and 5.7 g of Na2HPO4 were added to each liter of deionized water. A regulated DC power supply was used to control the voltage to -0.619 V, and the organic wastewater was electrolyzed for 24-72 hours. After the biofilm was formed, the power supply was disconnected, and an appropriate amount of feed liquid was taken out from the reactor at 24 hours and 72 hours, respectively, and various indicators of the feed liquid were tested. The feed liquid analysis method was carried out in accordance with GB11914-89, and the chemical oxygen demand COD value was determined by the potassium dichromate method.
[0066] The operation method of the blank experiment is the same as above. Disconnect the power supply and write down the experimental values. The experimental data adopts the average value of 3 times.
[0067] The test results are shown in the following table:
[0068]
[0069] From the above table, we can know that the biochar-based porous three-dimensional electrode of the present invention treats the simulated high-load impact organic wastewater. The highest degradation rate of the 24-hour treatment is 35.0%, the lowest is 33.6%, and the average is 34.4%. The pH value of the feed liquid is 6.0-6.3, which effectively inhibits the acidification phenomenon caused by the high-load impact; the highest degradation rate of the 72-hour treatment is 56.7%, the lowest is 55.8%, and the average is 56.2%. The pH value of the feed liquid is 6.9-7.0, which is very significant in stabilizing the acid-base changes of the feed liquid. The test shows that the biochar-based porous three-dimensional electrode prepared by the method of the present invention using straw biomass is very effective in alleviating the acidification phenomenon of the reaction liquid caused by high-load impact, with low cost and easy industrialization.
[0070] Comparative Example 1
[0071] The method is basically the same as Example 1, except that in Comparative Example 1, the cross-linked layer 1 of the biochar-based porous three-dimensional electrode is prepared by ultrasonically dispersing 5 g of biochar-based electrode material, 1 g of acrylic resin emulsion and 15 mL of water for 30 min to form a uniform mixed system A, and heating and stirring the mixed system A at 115°C until it becomes viscous. That is, acrylic resin emulsion is used in both the cross-linked layer 1 and the cross-linked layer 2 of the biochar-based porous three-dimensional electrode. The obtained electrode is named PBC-4.
[0072] The biochar-based porous three-dimensional electrode obtained in Example 1 and Comparative Example 1 was placed as a cathode in a single-chamber anaerobic reactor, and an ordinary graphite plate electrode was used as an anode. Simulated organic wastewater with an initial COD concentration of 9987 mg / L and a pH value of 7.0 was injected. A regulated DC power supply was used to control the voltage to -0.619 V. After the organic wastewater was electrolyzed for 72 hours, the organic wastewater of the same specification was replaced and electrolysis was continued for another 72 hours. After the biofilm was formed, the power supply was disconnected, and an appropriate amount of feed liquid was taken out from the reactor at 72 hours in each of the two experiments, and various indicators of the feed liquid were tested. The feed liquid analysis method was carried out in accordance with GB11914-89, and the chemical oxygen demand COD value was determined by the potassium dichromate method.
[0073] The test results are shown in the following table:
[0074]
[0075] It can be seen from the above table: the degradation rate of the biochar-based porous three-dimensional electrode obtained in Example 1 for the treatment of simulated high-load impact organic wastewater is 57.1% in 72 hours; the degradation rate is 56.9% after the same specification organic wastewater is replaced for 72 hours, showing excellent degradation stability; the degradation rate of the biochar-based porous three-dimensional electrode obtained in Comparative Example 1 for the treatment of simulated high-load impact organic wastewater is 56.3% in 72 hours; the degradation rate is 53.5% after the same specification organic wastewater is replaced for 72 hours, and the degradation stability is relatively poor; the reason is: in Example 1, two self-crosslinkable materials are used in the cross-linking layer 1 and the cross-linking layer 2 of the biochar-based porous three-dimensional electrode. When the two layers are coated together, due to the effect of self-crosslinking, the physical stability of the obtained electrode is better, and there is no loss of electrode material after long-term use, so it shows a stable degradation ability for COD.
[0076] The biochar-based porous three-dimensional electrode obtained in Example 1-3 was placed as a cathode in a single-chamber anaerobic reactor, and an ordinary graphite plate electrode was used as an anode. Simulated organic wastewater with an initial COD concentration of 9987 mg / L and a pH value of 7.0 was injected, wherein the inoculated sludge (containing Methanosarcina and Methanobacterium) was taken from a laboratory anaerobic reactor, 30 g of glucose, 1 g of urea, 250 mg of NaCl, 100 mg of KCl, 4.5 g of NaH2PO4, and 5.7 g of Na2HPO4 were added to each liter of deionized water. A regulated DC power supply was used to control the voltage to -0.619 V, and the organic wastewater was electrolyzed for 24-72 hours. After the biofilm was formed, the power supply was disconnected, and the anaerobic digestion experiment was continued for 20 days in a 35°C water bath. Methane gas was collected by a gas collection bag, the volume of biomethane was determined by the drainage method, and the gas components were analyzed by a gas chromatograph.
[0077] The operation method of the blank experiment is the same as above. Disconnect the power supply and write down the experimental values. The experimental data adopts the average value of 3 times.
[0078] The test results are shown in the following table:
[0079]
[0080] As can be seen from the above table, for the treatment of simulated high-load impact organic wastewater, the biochar-based porous three-dimensional electrode of the present invention has a methane production increase rate of up to 98.1% in 24-hour treatment, a minimum of 96.2%, and an average of 97.15%; the methane production increase rate of up to 96.8% in 72-hour treatment, a minimum of 95.4%, and an average of 96.1%; the methane yield is significantly improved, and the reason is that the biochar-based porous three-dimensional electrode provided by the present invention increases the metabolic activity of methanogenic microorganisms, thereby significantly improving the methane yield.
[0081] The above is only a preferred implementation of the patent of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the patent of the present invention. These improvements and modifications should also be regarded as the scope of protection of the patent of the present invention.
Claims
1. Application of a biochar-based three-dimensional porous electrode in high organic load anaerobic digestion, characterized in that: The sewage is treated by electrolysis, and the biochar-based three-dimensional porous electrode is used as a cathode; The preparation method of biochar-based three-dimensional porous electrode material is as follows: The straw biomass powder is immersed in NH3·H2O solution for pretreatment, the pretreated straw powder is subjected to anaerobic pyrolysis to obtain straw native biochar, and the straw native biochar is then sequentially immersed in alkali solution, activated at high temperature, washed with acid solution, and washed with water to obtain the electrode material; The preparation method of the biochar-based three-dimensional porous electrode comprises the following steps: S1: The biochar-based three-dimensional porous electrode material is mixed with carboxymethyl chitosan and a solvent, and then dispersed evenly, and heated and stirred until viscous, to obtain a cross-linked layer 1 of the biochar-based porous three-dimensional electrode; wherein the addition ratio of the biochar-based three-dimensional porous electrode material to carboxymethyl chitosan and the solvent is (3-8) g: 1 g: (12-20) ml; S2: The biochar-based three-dimensional porous electrode material is mixed with an acrylic resin emulsion and a solvent, and then dispersed evenly, and heated and stirred until viscous, to obtain the second cross-linked layer of the biochar-based porous three-dimensional electrode; wherein the addition ratio of the biochar-based three-dimensional porous electrode material to the acrylic resin emulsion and the solvent is (2-5) g:2 g:(14-20) ml; S3: Rolling the cross-linked layer 1 and the cross-linked layer 2 of the biochar-based porous three-dimensional electrode onto the upper and lower surfaces of the metal mesh respectively, and drying them to obtain the biochar-based porous three-dimensional electrode.
2. The use according to claim 1, characterized in that: In the pretreatment, the concentration of NH3·H2O solution is 10-20%, and the immersion time is ≥24 hours; the immersion ratio of straw biomass powder to NH3·H2O solution is 25g:(300-600)mL; In the alkali solution impregnation, the alkali solution is a NaOH solution with a concentration of 5-10%, and the impregnation time is ≥24 hours; the impregnation ratio of straw biomass powder to alkali solution is 10g: (35-60)mL; In the acid cleaning, the acid is a HCl solution with a concentration of 10-25%, and the acid cleaning time is 5-20 minutes; the cleaning ratio of straw biomass powder to acid is 10g:(85-120)mL.
3. The use according to claim 1, characterized in that: The anaerobic pyrolysis conditions are: in a nitrogen atmosphere, the heating rate is 1-5℃·min -1 , pyrolysis temperature 300~700℃, pyrolysis time 2h; The high temperature activation conditions are: heating rate 3-8℃·min -1 , activation temperature 850-1000℃, activation time 0.5-2h.
4. The use according to claim 1, characterized in that: The electrode material has a particle size of 100-200 μm, a particle hardness of ≥85%, and an apparent density of 0.5-2.0 g / cm 3 , specific surface area 500-700m 2 ·g -1 .
5. The use according to claim 1, characterized in that: In step S1, the preparation method of the carboxymethyl chitosan is as follows: chitosan is swelled with isopropanol for 0.5-1.5h and then alkalized, then an isopropanol solution containing sodium chloroacetate is added, and the reaction is carried out at 45-67°C for 4-6h; the pH of the system is adjusted to neutral and then allowed to stand; after removing the supernatant, the solution is filtered by suction, and the residue is dissolved with water and then filtered to remove impurities, rotary evaporated, ethanol is added to the filtrate under stirring until a large amount of flocs are precipitated, allowed to stand and then centrifuged for washing, and dried at 50-70°C to obtain carboxymethyl chitosan; The addition ratio of chitosan, isopropanol and isopropanol solution containing sodium chloroacetate is: 1g:(8-15)ml:(7-12)ml; and in the isopropanol solution containing sodium chloroacetate, the ratio of sodium chloroacetate to isopropanol solution is (3-6)g:10ml.
6. The use according to claim 5, characterized in that: The specific method of the alkalization treatment is: dropwise adding 110-140 ml of 10 mol / L NaOH solution into the system, and stirring at room temperature for 1.5-3 hours.
7. The use according to claim 1, characterized in that: In steps S1 and S2, the heating temperature is 110-125° C.; in step S3, the drying condition is: drying at 40-60° C. for 18-30 hours.
8. The use according to claim 1, characterized in that: In step S3, the pore size of the metal mesh is in the range of 0.5-1.5 mm.
Citation Information
Patent Citations
Preparation method and application of biomass porous carbon plate based on kapok fibers
CN107098327A
Secondary battery current collector and secondary battery using same
CN110098409A